Penerapan Tax Earmaking Pada Pajak Kendaraan Bermotor (PKB) Di Provinsi Sulawesi Selatan - Andi Pattarani (Universitas Muhammadiyah Makassar, 2018)
The research described in this final project aims to determine the application of tax allocation to motor vehicle taxes in the province of South Sulawesi. The type of research used is descriptive qualitative, i.e. the author takes special data obtained from observations and interviews conducted from August 9, 2018 to August 23, 2018. After analyzing and discussing the problem, the authors conclude that the application of tax earmarking has not been implemented on motor vehicle taxes in South Sulawesi province as they still encounter obstacles to a single unit of original regional revenue (PAD) which translates into all regional taxes. Tax revenue being mixed into one and it will be difficult to allocate motor vehicle tax revenue to tax allocation